The disordered structure of Q′ and C phases in Al–Mg–Si–Cu alloy. (June 2016) - Ding, Lipeng; Hu, Hai; Jia, Zhihong; Weng, Yaoyao; Wu, Xiaozhi; Liu, Qing
Abstract: The disordered structures of the Q′ and C phases in the over-aged Al–Mg–Si–Cu alloy were studied by the atomic resolution high-angle annular dark-field scanning transmission electron microscopy and density functional theory calculations. A Cu cluster-like zone is found in both the well-ordered and disordered regions of the disordered precipitates, which acts as a stable skeleton of these phases. The statistic result shows that the C phase is more preferential to produce disordered structure than the Q′ phase. The mechanism for forming the highly disordered C phase is attributed to the relatively weak metallic bonding between the Al–Si1 and Mg2–Si1 atoms. Graphical abstract: